Eco-friendly production of silica particles and fertilizer from rice husk, rice straw, and corncob wastes - Rafiq Usdiqa Maulana; Sania Isma Yanti; Riyanti Zhafirah Makrudi; Tunjung Mahatmanto; Untung Murdiyatmo (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Agroindustrial wastes represent a rich and underutilized source of valuable minerals. Because the amount of biomass wastes generated by the agroindustry is increasing and the demand for sustainability is arising, there is a growing need for improving agroindustrial waste utilization and valorization. One of the major industrial interests has been obtaining silica from biomass wastes. The synthesis of silica from agroindustrial waste materials typically involves the use of high energy input for calcination or incineration and chemicals for extraction. To reduce energy consumption and chemical waste generation, we modified a sol-gel method to yield a by-product that can be used as a fertilizer. High purity silica was obtained from rice husk (95.1%), rice straw (91.4%), and corncob (95.9%). The silica particles were amorphous and white in color. The mean diameters of the silica particles obtained from rice husk, rice straw, and corncob were 72.4, 68.1, and 52.9 µm, respectively. The acid waste generated from the process was neutralized to yield potassium chloride. This by-product had mineral contents that could be used for inorganic fertilizer. In addition to supporting sustainability, the development of agroindustrial waste utilization methods is important for the establishment of inexpensive processes that are adaptable for large-scale manufacturing.